Technology and knowledge transfers to dairy farms: Private sector contribution to improve milk production - Ibnu Budiman; Aditya Alta (Center for Indonesian Policy Studies (CIPS), 2022)
Indonesia's fresh milk production is only able to fulfil 22% of national milk demands. With growing milk consumption and the national target of fulfilling at least 60% of national demands from domestic production by 2025, boosting the productivity of dairy farms becomes important. This requires more adoption of productivity-enhancing technologies, techniques, and better farm management practices by dairy farms. However, as dairy farmers are predominantly smallholders, investing in technologies is a challenge due to cost, small production scale, and a lack of information and awareness. Partnering with the private sector offers a solution, as evidenced by case studies of technology and knowledge transfers from major milk-processing companies such as Cimory, Frisian Flag Indonesia [FFI], and Nestlé), and international development organizations operating in West Java and East Java. An example of collaboration is a support for digitalization in milk collection points (MCP). The system assigns a price that reflects the quality of milk from each farmer, therefore incentivizing investment in technology, equipment upgrading, and better management by farmers to improve milk quality and production. Different contract mechanisms are applied for the technology transfers-some are put alongside a supplier agreement with mandatory supply requirements while the others are delivered as grants and loans tied to a commitment to maintaining quality and standards.
Keywords: 330; Milchviehhaltung; Milchverarbeitung; Technischer Fortschritt; Technologietransfer; Privatwirtschaft; Indonesien